Onychodystrophy On Twenty Nails Caused By Candida Parapsilosis and Staphylococcus Aureus: A Case Report - Ariani, Tutty (Health and Medical Journal, 2022)
Introduction: Onychodystrophy can caused by variety of underlying diseases such as fungal and nonfungal infections, various noninfectious inflammatory dermatologic diseases of the nail unit and tumors.  To establish the underlying disease leading to nail dystrophy as a first step one should differentiate between infectious and noninfectious disorders by obtaining nail material for microscopic examination and culture.  Case Report: A case of onychodystrophy on twenty nail in 43 years old housewife woman was reported.  The chief complaint was all of her fingernails and toenails were brittle, the color became yellow brown blackish since 6 month ago and sometimes excreted smell discharge. There were onychodystrophy, onycholysis, subungual hyperkeratosis and yellow brown blackish discolorization of all fingernails and toenail on physical examination. There were longitudinal striae, aurora borealis pattern, jagged margin of proximal edge on dermoscopic examination. Microscopic examination of nail clipping and scrapping of fingernails with 20 % potassium hydroxide was negative. The culture of fungi showed Candida Parapsilosis. Culture of bacteria was Staphylococcus aureus. PAS stain from nail clipping resulted was Candida Spp. Patient treated with oral pulse antifungal itraconazole 2x200 mg/day combination with ciprofloxacin 2x500 mg twice a day and ketokonazol cream twice a day. Conclusion: Onychodystrophy can caused by onychomycosis aggravated by bacterial infection. Diagnosis of onychomycosis candida was made base on diagnosis, physical examination, microscopic, culture and histopatology. Predisposition factor in this patient was chronic exposure with water. There is improvement clinical appearance after therapy with antifungal and antibiotic